Spectrophotometric Methods for the Determination of Ascorbic acid - Suryanarayana Rao, V.; Rama Devi, B. (Asian Journal of Chemistry, 2010)
Ascorbic acid can be determineo In trace quantities based on its reactions with vanadium(V), iron(III)-thiocyanate complex, alkaline potassium ferricyanide and potassium permanganate. Probable explanations are given.